Influence of Moderate and Severe Exercise on Memory Formation and Anxiety-like Behaviors in Male Wistar Rat - Alipour, Vahide; Shabani, Ramin; Zarrindast, Mohammad Reza; Rahmani-Nia, Farhad; Nasehi, Mohammad (Archives of Advances in Biosciences, 2019)
Introduction: Recent researchers have showed that regular exercise induces positive effects on cognitive functions. Exercise intensity and timing of cognitive assessment may have an interactive effect on cognitive changes. Previous researches suggest that moderate intensity treadmill running has the most consistent benefit to cognitive function. In contrast, studies find positive, negative, or null effects to cognitive function after high intensity treadmill running. The primary objective of the present study was to compare the cognitive effects of intensity treadmill running protocol 1 (Low intensity), protocol 2 (Moderate intensity) and protocol 1 plus 2 (High intensity).Materials and Methods: Male Wistar rats were divided into four groups (n=7 in each group) including: sedentary (Non-exercise), protocol 1, protocol 2, and combination of protocol 1 and 2. Step-through passive avoidance and elevated-plus maze apparatus have been used to test parameters of passive avoidance learning and anxiety-like behaviors. Results: These findings showed that combination of both protocols (Protocol 1 with protocol 2) decreased step-through latency in the passive avoidance apparatus indicating memory impairment [P<0.05]. Moreover, the data revealed that different protocols for exercises did not alter %OAT [P<0.001], %OAE %OAT [P>0.05] and locomotor activity %OAT [P<0.05] compared to control group but not others. Conclusion: High intensity exercise not only induced beneficial effect but also impaired memory formation.